Parvovirus B19 (PB19) – is the infection associated with connective tissue diseases in adults and children? - Szumera, Małgorzata (Reumatologia/Rheumatology, 2005)
Parvovirus B 19 is the cause of erythema infectiosum, aplastic anaemia, neonatal anaemia, thrombocytopenia, leukopenia. The course of infection is biphased, after flulike symptoms arthritis or pancytopenia may occur, more often in women than men and children. Laboratory diagnosis consists of detection of immunoglobulins M and G against capsid proteins VP2, VP1 and NS-1. Serological status and time of infection can be established this way. None the less the most specific is the detection of PB 19 DNA by hybrydization and polymerase chain reaction assays which are positive even in distant time from infection and in immunocompromised patients Protractive arthritis may follow the infection leading to diagnosis of rheumatoid or juvenile idiopathic arthritis. The coincidence of PB 19 infection and joint lesions may suggest its etiology. The irrefutable prove was not assessed, yet seropositive RA and JIA as a result of PB 19 infection were introduced so far. Some authors discussed the problem of other connective tissue diseases following PB 19 infection. As long as the prove will be obtained PB19 should be searched for in arthropathies and all PB 19 positive patients with protracted arthritis should be controlled.